PENGARUH FAKTOR SOSIAL DAN EKONOMI TERHADAP PENDAPATAN BUDIDAYA IKAN BANDENG DI KECAMATAN PADEMAWU KABUPATEN PAMEKASAN - Hakim, Rachman; Gazali, Gazali; Syaifadi, Febryan (Creative Research Management Journal, 2023)
Milkfish cultivation has a significant economic impact in Pademawu District. However, milkfish cultivators often encounter many obstacles during the cultivation process to selling it. This study aims to determine the effect of social and economic factors on the income of the milkfish farming community in Pademawu District, Pamekasan Regency. This study uses a quantitative approach. The population in this study were 30 Pademawu people who cultivate milkfish. The data collection technique used was a questionnaire. The data analysis technique used is multiple linear regression analysis. The sampling technique uses a full sample, meaning that the entire study population is used as a sample. The results showed that social and economic factors had a positive effect on the income of the milkfish farming community in Pademawu District, Pamekasan Regency. Social and economic factors also simultaneously influence the income of the milkfish farming community in Pademawu District, Pamekasan Regency. Economic factors have the most dominant influence on the income of the milkfish farming community in Pademawu District, Pamekasan Regency. The practical implication of the results of this research is that milkfish cultivators must understand very well the importance of economic factors, one of which is capital. Farmers need to have sufficient capital so as not to interfere with the process of milkfish cultivation. The local government can also help find solutions related to capital, for example by establishing a cooperative for milkfish cultivators in Pademawu District, Pamekasan Regency.